Endothelial cell elongation and alignment in response to shear stress requires acetylation of microtubules - Moise, Katiannah; Arun, Keerthana M.; Pillai, Maalavika; Salvador, Jocelynda; Mehta, Aarya S.; Goyal, Yogesh; Iruela-Arispe, M. Luisa (Frontiers in Physiology, 2024)
The innermost layer of the vessel wall is constantly subjected to recurring and relenting mechanical forces by virtue of their direct contact with blood flow. Endothelial cells of the vessel are exposed to distension, pressure, and shear stress; adaptation to these hemodynamic forces requires significant remodeling of the cytoskeleton which includes changes in actin, intermediate filaments, and microtubules. While much is known about the effect of shear stress on the endothelial actin cytoskeleton; the impact of hemodynamic forces on the microtubule network has not been investigated in depth. Here we used imaging techniques and protein expression analysis to characterize how pharmacological and genetic perturbations of microtubule properties alter endothelial responses to laminar shear stress. Our findings revealed that pharmacological suppression of microtubule dynamics blocked two typical responses to laminar shear stress: endothelial elongation and alignment. The findings demonstrate the essential contribution of the microtubule network to changes in cell shape driven by mechanical forces. Furthermore, we observed a flow-dependent increase in microtubule acetylation that occurred early in the process of cell elongation. Pharmacological manipulation of microtubule acetylation showed a direct and causal relationship between acetylation and endothelial elongation. Finally, genetic inactivation of aTAT1, a microtubule acetylase, led to significant loss of acetylation as well as inhibition of cell elongation in response to flow. In contrast, loss of HDAC6, a microtubule deacetylase, resulted in robust microtubule acetylation with cells displaying faster kinetics of elongation and alignment. Taken together, our findings uncovered the critical contributions of HDAC6 and aTAT1, that through their roles in the regulation of microtubule acetylation, are key mediators of endothelial mechanotransduction.